The Class F of G Protein-Coupled Receptors: International Union of Basic and Clinical Pharmacology CXV - Joshi Ankur; Soni Priyanka; Khemani Purva; Malviya Neelesh; Malviya Sapna; Kharia Anil (Revista Electronica de Veterinaria, 2024)
There are ten Frizzleds (FZD1–10) and one Smoothened (SMO) G protein-coupled receptor (GPCR) in class F. Hedgehog (Hh) family morphogens acting on the transmembrane protein Patched indirectly activate SMO, while secreted lipoglycoproteins of the Wingless/Int-1 (WNT) family bind and activate FZDs. An update is warranted due to the progress made in our knowledge of FZDs and SMO as molecular machines and dynamic transmembrane receptors in the fourteen years since the first-class F GPCR IUPHAR nomenclature report. Recent developments in molecular pharmacology and structural biology have shed light on the mechanisms of ligand identification, receptor activation, signal initiation, and signal specification, among other areas. In addition, class F GPCRs are still being worked on as potential therapeutic targets, and new methods and technologies including CRISP/Cas9 edited cell systems and genetically encoded biosensors have helped to improve the functional analysis of these receptors. Cryogenic electron microscopy and crystal structure analysis have advanced to the point that our understanding of structure-function correlations is rapidly expanding, which is fantastic news for the pharmaceutical industry. The intricacy of the WNT/FZD and Hh/SMO signaling pathways is still not completely understood, despite the advances.A great deal of structural and functional information regarding the activation processes of Frizzleds and Smoothened has been uncovered in the last several years of research. The discovery expands our knowledge of the molecular mechanisms involved in ligand recognition, receptor activation, signal specification, and initiation, and it also opens up new avenues for the use of biologics and small molecule drugs in regenerative medicine and therapy by targeting class F GPCRs.